Evaluating the immune response in a murine cancer model between irreversible electroporation and an advanced biphasic pulsed electric field technology - Nafie, Ebtesam H. O.; Pastori, Chiara; Neal, Robert E. (Frontiers in Oncology, 2025)
IntoductionNon-thermal ablation, including irreversible electroporation (IRE) and Aliya®, an advanced biphasic pulsed electric field (aPEF) technology, have emerged as effective tumor ablation approaches, particularly in sensitive anatomical locations. These methods not only ablate tumors but also may stimulate immune responses.MethodsThis study compares the immunological impact of biphasic aPEF and IRE in a murine breast cancer model. Equal-sized tumor ablations were performed using both technologies, followed by analysis of cytokine profiles, immune cell populations, tumor growth, and overall survival.ResultsaPEF induced a differentiated tumor microenvironment four days post-ablation compared to IRE, with greater intratumoral infiltration of T-cells, B-cells, increased M1 macrophages, and decreased myeloid-derived suppressor cells. Analysis of systemic circulating immunocytes 14 days post-ablation showed elevated levels of B-cells, CD4 and CD8 T-cells (including memory subpopulations) in the aPEF-ablated groups. aPEF also resulted in better control of ablated and contralateral tumor growth, leading to improved median survival.DiscussionThis study demonstrates that the specific biphasic aPEF system evaluated here induces a stronger immunostimulatory effect and superior tumor control compared to IRE, supporting the notion that not all non-thermal ablation is equal, and each may be better suited to different objectives. Further clinical investigations into the potential for better clinical outcomes from this specific advanced pulsed electric field technology is warranted.